General physics : for senior high school 2 - Nenita D. Makalintal (Malabon City : Mutya Publishing House, Inc., 2018)
"This book is composed of 12 chapters intended for use by kto12 students. The concepts, principles and laws discussed in each chapter were presented with corresponding illustrations to give more insights and help students acquire more scientific knowledge and understanding that would enable them to solve real life situation problems."
Includes bibliography.
English text.
Keywords: Physics